Study on “Metamaterial” Structural Absorbing Composite Technology - LI Song-ming; JIANG Shi-cai; WANG Yong-lin; GU Jian-xiao; XING Li-ying (Cailiao gongcheng, 2017)
The process technology and the mechanical and electrical properties of the "metamaterial"structural absorbing composites were studied, in which metal periodic structure units were produced on the organic carrier film and then combined with medium. Through the breakthrough of key technologies involving producing different size metal periodic structure, the transfer of metal periodic structure, and optimizing process parameters, the "metamaterial" structural absorbing composite with good wave-absorbing and mechanical stabilities that contained multi-layer metal periodic structure was prepared. The "metamaterial" structural absorbing composite has a high broadband absorbing property in the frequency range of 2-18GHz.